Marine turtles, umbrella species undergoing recovery - Gallegos-Fernández, Sandra A.; Trujillo-Córdova, Jorge A.; Guzmán-Hernández, Vicente; Abreu-Grobois, F. Alberto; Huerta-Rodríguez, Patricia; Gómez-Ruiz, Pilar A.; Uribe-Martínez, Abigail; Cuevas, Eduardo (Frontiers in Amphibian and Reptile Science, 2023)
Marine turtles inhabit various coastal and marine ecosystems and play significant ecological roles throughout their life cycles. Because of the significant overlap with other species at risk in their geographic ranges, the successful conservation of marine turtles also protects numerous co-occurring species, a phenomenon known as the "umbrella species effect." Since several marine turtle populations have shown positive trends, suggesting incipient recovery, it is expected that their umbrella characteristics will coevolve as their populations grow and expand. Recognizing the considerable potential of marine turtles as umbrella species, we advocate for promoting this concept and explicitly integrating it into management and recovery programs. This approach would facilitate concurrent benefits not only for marine turtles but also for other species and their associated habitats. To achieve this goal, we analyzed the conservation status of marine turtles in the Gulf of Mexico and Western Caribbean within the framework of the legal regulations. Additionally, we reviewed the current challenges in marine turtle recovery in the framework of ecological restoration, while also aiming to target and encourage their utilization as umbrella species.